An on‐surface Diels–Alder reaction. (10th November 2021) - Castro‐Esteban, Jesús; Albrecht, Florian; Fatayer, Shadi; Pérez, Dolores; Gross, Leo; Peña, Diego
Abstract: The Diels–Alder reaction is one of the most popular reactions in organic chemistry. However, its use in the field of on‐surface synthesis is hampered by the spatial restrictions of this cycloaddition reaction. Herein we selected a cyclic strained triyne to demonstrate an on‐surface hexadehydro‐Diels–Alder reaction in a single molecule. The reaction was studied in detail by means of atomic force microscopy (AFM) with CO‐functionalized tips. Our results pave the way to use this iconic pericyclic reaction for on‐surface synthesis, introducing the concept of atom economy in the field. Abstract : A hexadehydro‐Diels–Alder reaction was demonstrated on‐surface in single molecules of a cyclic strained triyne. The starting material, several intermediates and the product were visualized by means of atomic force microscopy (AFM) with CO‐functionalized tips. Our results pave the way to use this iconic pericyclic reaction for on‐surface synthesis, introducing the concept of atom economy in the field.